Taxes and Liabilities Paid by Turkestan is to the Russian Empire's Treasury - Ikromjon Azizov (International Journal on Integrated Education, 2021)
The article states that the large number of taxes and obligations paid by Turkestanis to the treasury of the Russian Empire made it difficult for the population to pay these taxes. When introducing the tax system in Turkestan, the Russian Empire did not take into account the beliefs of the inhabitants of the region and the centuries-old traditions of the tax system, natural and climatic conditions. at the same time, it recouped the costs of colonial policy without developing economic infrastructure in the country by increasing taxes year by year.